Parental Sociodemographic Factors Associated with Stunted Children below 5 Years of Age in Kampar Indonesia - Yefri, Riza; Lipoeto, Nur Indrawaty; Putra, Andani Eka; Kadim, Muzal (Open Access Macedonian Journal of Medical Sciences, 2022)
BACKGROUND: The prevalence of stunted children under 5 years in Riau Province exceeds 27.35% and Kampar District contributed the highest prevalence rate (32.05%) compared to other districts in Riau Province. AIM: This study aims to analyze the parental sociodemographic factors of parents associated with stunting children in Kampar District, Riau Province in Indonesia. METHODS: This type of research is a case-control study on stunted children in Kampar Regency aged under 5 years. Control group was selected by matching process include age, gender, residence, and socioeconomic status. Anthropometric measurements performed and calculated using the World Health Organization Anthro (version 3.2.2, October 2020) include weight-for-age z-score (WAZ), height-for-age z-score (HAZ), weight-for-height z-score (WHZ), and body mass index. The analysis carried out includes univariate and bivariate analysis to find the relationship between the independent variable and the dependent variable. RESULTS: Approximately 139 children aged 2 to 59 months consist of stunted (68) and nonstunted (71) groups. Among the 68 stunted children, 31 (41.3%) were very stunted. The stunted group had decreased in WAZ, HAZ, and WHZ, but only HAZ was statistically significant (p < 0.05). Lower mother’s height and education were determined of parental sociodemographic factors associated with stunting and increased risk of stunted children in Kampar (odds ratio [OR] 3.02 and OR 2.50, 95% confidence interval, respectively). CONCLUSIONS: Lower maternal’s height and education were determine parental sociodemographic factors associated with stunting in Kampar.